THE EFFECT OF WASTE BAGASSE (Saccharum sp) FERTILIZER TOWARD GROWTH OF PEANUTS (Arachis hypogaea L.) - Emas Agus Prastyo Wibowo; Wening Dwi Prastiwi; Dina Fika Nada; Yuni Nur Azizah (Agrotech Journal, 2017)
The process of sugar cane into sugar which is carried out in the sugar mill produces bagasse obtained from the milling process around 32% of the total cane processed. Sugarcane production in Indonesia in 2007 amounted to 21 million tons, the potential of bagasse produced about 6 million tons of bagasse per year. Up untill now almost every cane sugar mills uses bagasse as boiler fuel, animal feed mixes and the rest are burned or thrown away. One of alternative solid waste management is to turn solid waste into compost.The purpose of this research is to understand the effect of bagasse fertilizer on growth and progress of peanut plants (Arachis hypogaea L.). Bagasse fertilizer made using cow dung as bioactivator. Bagasse obtained from several places in Semarang mashed with finely enough size. Then, with a ratio of cow dung and bagasse 1: 3. Placed in a container then mix and sealed until there is no incoming air. Every 4 or 5 days in 4 weeks is being inverted. After 4 weeks it will get bagasse fertilizer with characteristic brown color, odorless and slightly moist. This research uses three treatments there are peanuts with mixed bagasse fertilizer on the soil medium, compost on the soil medium, and without fertilizer then measured the progress for 14 days. After 14 days, so it obtained an average of plants height and number of leaves. Respectively, are 2.10; 1.38; 2.24 while the number of leaves are 2.55; 2.66; 3.22